2001
DOI: 10.1053/jhep.2001.25546
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine motility factor enhances hepatoma cell invasion across the basement membrane through activation of β1 integrins

Abstract: Autocrine motility factor/phosphohexose isomerase (AMF/PHI) is a cytokine that is linked to tumor invasion and metastasis. In hepatocellular carcinoma (HCC) tissues, hepatoma cells produce AMF/PHI and its receptor, Mr 78,000 glycoprotein (gp78), is strongly detected in hepatoma cells invading into the stroma and tumor thrombi in the portal vein. Here, we investigated the mechanism of hepatoma cell invasion through Matrigel induced by AMF/PHI using 3 hepatoma cell lines. Production of AMF/PHI, phosphorylation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 32 publications
2
41
0
Order By: Relevance
“…AMF/PHI also stimulates MMP-2 secretion and extracellular MMP-2 activation, being related to destruction of the basement membrane followed by metastasis and invasion in hepatoma cells. 32 These mechanisms occurring in host organs also may contribute to AMF-regulated dissemination of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMF/PHI also stimulates MMP-2 secretion and extracellular MMP-2 activation, being related to destruction of the basement membrane followed by metastasis and invasion in hepatoma cells. 32 These mechanisms occurring in host organs also may contribute to AMF-regulated dissemination of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…30 Interestingly, transfection of AMF/PHI-tagged hemagglutinin into Cos7 cells reveals its intracellular localization within actin-rich pseudopodial domains. 31 Torimura et al 32 have demonstrated that AMF/PHI enhances Rho activity and phosphorylation of MEK1 and MEK2 in human hepatoma cell lines. Rho is one of the most important molecules in the AMF/PHI signal transduction.…”
mentioning
confidence: 99%
“…Therefore, enolase is a therapeutic target for many diseases, including candidiasis (7,55). Another extracellular glycolytic enzyme, phosphoglucose isomerase, enhances the motility of tumor cells (11) and performs like a cytokine (52), although it possesses no enzymatic activity outside the cell (54). However, the secretory pathway of glycolytic enzymes such as enolase and phosphoglucose isomerase remains to be revealed.…”
mentioning
confidence: 99%
“…C3 exoenzyme inhibited stress fiber formation accompanied by a decrease in active RhoA, indicating that AMFinduced cytoskeletal rearrangement is dependent on Rho activation. Torimura et al (2001) also demonstrated that, in human hepatoma cell lines, AMF/PGI enhanced Rho activity, which was slightly blocked by the functionblocking antibody for the integrin-b1 subunit.…”
Section: Introductionmentioning
confidence: 80%